2020
DOI: 10.3389/fimmu.2020.01487
|View full text |Cite
|
Sign up to set email alerts
|

AIM2 Inflammasome's First Decade of Discovery: Focus on Oral Diseases

Abstract: A common feature of many acute and chronic oral diseases is microbial-induced inflammation. Innate immune responses are the first line of defense against pathogenic microorganisms and are initiated by pattern recognition receptors (PRRs) that specifically recognize pathogen-associated molecular patterns and danger-associated molecular patterns. The activation of certain PRRs can lead to the assembly of macromolecular oligomers termed inflammasomes, which are responsible for pro-inflammatory cytokine maturation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
26
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(28 citation statements)
references
References 71 publications
(91 reference statements)
1
26
0
1
Order By: Relevance
“…One proposed hypothesis suggests that, in response to bacterial infection, type I IFN is synthesized and drives the expression of IFN regulatory factor 1 (IRF1) via an autocrine pathway through activation of the cyclic GMP-AMP synthase (cGAS)/stimulator of IFN genes (STING)/STING-TANK binding kinase 1 (TBK1)/IRF3 axis ( 27 ). Upon IRF1 expression, guanylate-binding protein 2 (GBP2)/GBP5 and immunity-related GTPase family member b10 (IRGB10) are produced and disrupt the bacterial membrane and vacuoles containing bacteria ( 26 , 28 ). Therefore, a large quantity of dsDNA is exposed and sensed by the AIM2 inflammasome.…”
Section: Structure and Activation Of Inflammasomesmentioning
confidence: 99%
“…One proposed hypothesis suggests that, in response to bacterial infection, type I IFN is synthesized and drives the expression of IFN regulatory factor 1 (IRF1) via an autocrine pathway through activation of the cyclic GMP-AMP synthase (cGAS)/stimulator of IFN genes (STING)/STING-TANK binding kinase 1 (TBK1)/IRF3 axis ( 27 ). Upon IRF1 expression, guanylate-binding protein 2 (GBP2)/GBP5 and immunity-related GTPase family member b10 (IRGB10) are produced and disrupt the bacterial membrane and vacuoles containing bacteria ( 26 , 28 ). Therefore, a large quantity of dsDNA is exposed and sensed by the AIM2 inflammasome.…”
Section: Structure and Activation Of Inflammasomesmentioning
confidence: 99%
“…The role of this complex is to liberate Cas1, which becomes active and cleaves pro-IL-1β and pro-IL-18 releasing active cytokines ( Harton et al, 2002 ; Ting et al, 2008 ; Schroder and Tschopp, 2010 ; Shenoy et al, 2012 ; Zheng et al, 2020 ). In addition to the release of cytokines, inflammasome activation is accompanied by a specific form of cell death called pyroptosis ( Wang et al, 2020 ). Pyroptosis is characterized by Cas1 cleavage of the gasdermin D (GSDMD) protein ( Broz, 2015 ), which leads to cell lysis and subsequent release of cytoplasmic components, including mature forms of IL-1β and IL-18 ( Sansonetti et al, 2000 ).…”
Section: Inflammasome Structurementioning
confidence: 99%
“…In normal inactive state, AIM2 HIN confines AIM2 PYD domain, restricting its ability to form PYD‐PYD interactions 84 . The binding of dsDNA to AIM2 HIN by oligonucleotide/oligosaccharide binding folds of HIN or independent interactions, release PYD domain further enabling it to form PYD‐PYD interactions 85 . Binding of AIM2 PYD to ASC completes the formation of an active inflammasome assembly to perform downstream actions.…”
Section: Inflammasome Pathwaymentioning
confidence: 99%
“…84 The binding of dsDNA to AIM2 HIN by oligonucleotide/oligosaccharide binding folds of HIN or independent interactions, release PYD domain further enabling it to form PYD-PYD interactions. 85 Binding of AIM2 PYD to ASC completes the formation of an active inflammasome assembly to perform downstream actions. However, few studies contradicted the autoinhibitory model of AIM2 PYD activation, the studies suggested the oligomerization-driven activation of AIM2 PYD assembly.…”
Section: Aim2 Inflammasomementioning
confidence: 99%